Motorcycle couriers from the city of Porto Alegre: living together with traffic accident risks - Andréa Márian Veronese (Online Brazilian Journal of Nursing, 2006)
This paper aim at investigating how motorcycle couriers see the risk of traffic accident in their daily work in the city of Porto Alegre, Brazil. The study was based on sociological theories about “risk”, especially those that emphasize the social and cultural character of their meanings 1 2. In this sense, the research had as presupposition the idea that “risk” is a concept that may be defined by the subject himself who is involved in the risk situation 3. The research was developed into a qualitative perspective and followed the methodological procedures of the Grounded Theory 4. The focus group 5 technique was the strategy used for the data collection. The results of the information analysis point out that the meanings of the “risk of a traffic accident” are conditioned to the way whereby the motorcycle couriers see the phenomenon at issue and to the circumstances in which this phenomenon takes place, which includes the people that are involved. The data also suggest that the motorcycle couriers show contradictory meanings to the risks of traffic accidents. According to them, the risk may have negative and/or positive implications. Motorcycle couriers recognize the risks of traffic accidents when they take over the tasks attributed to the motorcycle courier’s work and take over the risks of such tasks. The risks of traffic accident are produced by social and personal interests; social in the sense of the demands for urgency and speed and personal in relation to the interest of earning a higher income and to be the fastest motorcycle courier. Based on the analyzed data, one concludes that the motorcycle couriers consider the risks of traffic accident inherent to the day-to-day work and they use self-care strategies to live along with these risks.